2016
DOI: 10.1080/02668734.2015.1107123
|View full text |Cite
|
Sign up to set email alerts
|

Pluralistic approaches to the study of process and outcome in psychoanalysis. The LAC depression study: a case in point

Abstract: Approaching process and outcome in psychoanalysis is a topic that touches on ambitious and complex epistemological and methodological issues. As discussed in the first part of the paper, in keeping with challenging epistemic considerations, it would seem appropriate to describe the specificity of psychoanalysis as a specific scientific discipline of the unconscious (spezifische Wissenschaft des Unbewussten, see LIT). Psychoanalysis, over its more than 100-year history, evolved a range of highly advanced resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In fact, it is important to acknowledge that Solms (2020) has recently provided an example of how to use concepts from cognitive psychology (i.e., nondeclarative memory) to study the clinical phenomenon of psychoanalytic process. Others (Jiminez and Altimir 2020; Leuzinger-Bohleber, Kallenbach, and Schoett 2016) also agree that psychoanalytic process can be examined within a natural science model. And Jaffe (2021) has shown that the importance of working through in clinical analysis can be understood using the cognitive concept of procedural memory.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it is important to acknowledge that Solms (2020) has recently provided an example of how to use concepts from cognitive psychology (i.e., nondeclarative memory) to study the clinical phenomenon of psychoanalytic process. Others (Jiminez and Altimir 2020; Leuzinger-Bohleber, Kallenbach, and Schoett 2016) also agree that psychoanalytic process can be examined within a natural science model. And Jaffe (2021) has shown that the importance of working through in clinical analysis can be understood using the cognitive concept of procedural memory.…”
Section: Discussionmentioning
confidence: 99%